Surface oil removal and electroplating process for ABS (Acrylonitrile Butadiene Styrene) plastic
Through plasma treatment and cymbal modification technology, the problem of low polarity and poor adhesion of ABS plastic surfaces, and through the improved vacuum electroplating coating, the efficiency and effect of ABS plastic plating process are improved, and better attachment strength has been achieved. , Flame retardant and water resistance.
Patent Information
- Application Number
- CN202411491484.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-01-24
AI Technical Summary
The ABS plastic surface has low polarity and poor adhesion, and the vacuum electroplating coating has low adhesion, poor flame retardant performance, difficult storage, and poor water resistance of the coating after curing.
The plasma treatment process is used to remove oil stains on the surface of the ABS plastic substrate, and the ABS plastic substrate is modified with 3-mercaptopropyltrimethoxysilane to improve its adhesion to the vacuum electroplating coating. Use an improved vacuum electroplating coating that contains bis-hydroxy silicon-containing flame retardant to improve the flame retardancy and water resistance of the coating.
It improves the efficiency and effect of ABS plastic surface degreasing and electroplating processes, enhances the adhesion between the substrate and the coating, improves the flame retardancy and water resistance of the coating, and reduces production costs.
Smart Images

Figure BDA0005100192830000121
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of plastic surface treatment, in particular to a surface degreasing and electroplating process for ABS plastic. Background Art
[0002] ABS plastic is a ternary copolymer of acrylonitrile (A), butadiene (B), and styrene (S). The relative content of the three monomers can be changed arbitrarily to make various resins. ABS plastic has the common properties of the three components, with good chemical corrosion resistance, heat resistance, surface hardness, high elasticity and toughness, and easy processing and molding characteristics. It has been widely used in manufacturing industries such as machinery, electrical, textile, automobile, aircraft, and ships, as well as chemical industry. With the development of technology, the demand for plastic decorations is also increasing. Metallization treatment of the surface of ABS plastic can not only give the material a metallic texture, but also reduce production costs.
[0003] Vacuum plating technology is safe, energy-saving, and low-pollution, and is a more environmentally friendly plastic surface metallization process. However, ABS plastic is a non-polar material with low surface polarity, so its adhesion is poor. Before processing, it needs to be treated to remove the oil attached to the surface. In addition, most vacuum plating coatings are acrylic resins, which not only have the problem of low adhesion to the ABS plastic substrate, but also have the disadvantages of poor flame retardancy, difficult storage, and poor water resistance of the coating after curing. Therefore, it is very necessary to modify the above problems to optimize the surface degreasing and electroplating process of ABS plastic. Summary of the invention
[0004] The object of the present invention is to provide a surface degreasing and electroplating process for ABS plastics to solve the problems raised in the above background technology.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: a surface degreasing and electroplating process of ABS plastic, comprising the following steps:
[0006] Step 1:
[0007] Plasma treatment is performed on the surface of the ABS plastic substrate to remove oil stains on the surface of the ABS substrate, thereby obtaining a surface-deoiled ABS plastic substrate;
[0008] Step 2:
[0009] Anhydrous ethanol, deionized water, ammonia water, and 3-mercaptopropyltrimethoxysilane are mixed, reacted in a water bath at 55-65° C. for 2-3 hours, and allowed to stand for 5-10 minutes after the reaction to obtain a mixed solution; an ABS plastic substrate with degreased surface is placed in the mixed solution, soaked for 1-2 hours, taken out, rinsed with anhydrous ethanol and deionized water, and dried to obtain a thiol-grafted ABS plastic substrate;
[0010] Step 3:
[0011] The vacuum electroplating coating is sprayed on the mercapto-grafted ABS plastic substrate, dried naturally for 2 to 3 minutes after spraying, dried in an oven at 50 to 60°C for 3 to 5 minutes, and then UV cured; the metal electroplating layer is formed by vacuum electroplating to obtain an ABS plastic electroplated part;
[0012] Step 4:
[0013] Post-processing of ABS plastic electroplated parts.
[0014] Furthermore, in step 1, the vacuum degree of the plasma treatment is 100-120 Pa, the treatment time is 3-5 min, and the power is 100-110 W.
[0015] Furthermore, in step 2, the weight ratio of anhydrous ethanol, deionized water, ammonia water, and 3-mercaptopropyltrimethoxysilane in the mixed solution is (50-60):10:(0.6-0.8):(0.4-0.5).
[0016] Furthermore, in step 3, the method for preparing the vacuum electroplating coating comprises the following steps:
[0017] S1: Under nitrogen environment, phosphorus oxychloride was dissolved in tetrahydrofuran, triethylamine was used as an acid binding agent, 2-aminobenzothiazole was added under ice bath condition of 0-5°C for reaction for 2-3h, the temperature was raised to 30-40°C for reaction for 3-4h, acrylamide was added, the temperature was continued to be raised to 45-60°C for reaction for 10-12h, and a flame retardant intermediate was obtained;
[0018] S2: The flame retardant intermediate and 1,1,3,3-tetramethyldisiloxane are mixed and dispersed in tetrahydrofuran, and an isopropanol solution of chloroplatinic acid is used as a catalyst, and the mixture is reacted at 55-65° C. in an argon environment for 8-10 hours, and allyl alcohol is added for end-capping reaction for 6-10 hours to obtain a dihydroxy silicon-containing flame retardant;
[0019] S3: polyethylene glycol 2000 and a dihydroxy silicon-containing flame retardant are mixed to obtain a mixed diol; isophorone diisocyanate is added to the mixed diol at a molar ratio of hydroxyl group to isocyanate group of 1:(1.5-2), dibutyltin dilaurate is used as a catalyst, and the mixture is reacted at 70-80° C. for 2-3 hours to obtain a silicon-containing polyurethane prepolymer; the temperature is lowered to 50-60° C., hydroxyethyl acrylate is added to the silicon-containing polyurethane prepolymer at a molar ratio of hydroxyl group to isocyanate group of 1:1, and the mixture is reacted for 1-2 hours to obtain a polyurethane acrylic resin oligomer;
[0020] S4: Mix polyurethane acrylic resin oligomer, methyl methacrylate, 1,6-hexanediol diacrylate, trimethylolpropane trimethacrylate, photoinitiator, defoamer, leveling agent, ethylene glycol propyl ether, ethyl acetate, butyl acetate, isobutyl alcohol and deionized water, and filter with 300-400 mesh gauze to obtain vacuum electroplating coating.
[0021] Furthermore, in S1, the molar ratio of phosphorus oxychloride, 2-aminobenzothiazole and acrylamide is 1:1:2.
[0022] Furthermore, in S2, the molar ratio of the flame retardant intermediate, 1,1,3,3-tetramethyldisiloxane, and allyl alcohol is 1:2:2.
[0023] Furthermore, in S3, polyethylene glycol 2000 and dihydroxy silicon-containing flame retardant are mixed in a weight ratio of (3-4):1 to obtain a mixed diol.
[0024] Furthermore, in S4, the amount of each component, by weight, is 40 to 60 parts of polyurethane acrylic resin oligomer, 3 to 5 parts of methyl methacrylate, 6 to 12 parts of 1,6-hexanediol diacrylate, 5 to 8 parts of trimethylolpropane trimethacrylate, 2 to 3 parts of photoinitiator, 0.5 to 1 part of defoaming agent, 0.5 to 1 part of leveling agent, 0.5 to 1 part of ethylene glycol propyl ether, 12 to 15 parts of ethyl acetate, 8 to 10 parts of butyl acetate, 7 to 10 parts of isobutanol, and 20 to 25 parts of deionized water.
[0025] Furthermore, in step 3, the spraying pressure is 4-6 kg / cm 2 , spraying distance is 10-15cm, spraying thickness is 7-9μm; UV curing exposure energy is 600-800mJ / cm 3 The processing time is 10 to 15 seconds.
[0026] Furthermore, in step 3, the vacuum electroplating temperature is 50-60° C., and the thickness of the metal electroplating layer is 20-50 μm.
[0027] Furthermore, in step 4, the post-treatment method is to perform a plasma treatment process on the surface of the ABS plastic electroplated part, the vacuum degree of the plasma treatment is 150-200 Pa, the power is 800-900 W, and the treatment time is 3-5 min.
[0028] Compared with the prior art, the beneficial effect achieved by the present invention is that the present invention uses a plasma treatment process to remove oil stains on the surface of ABS plastic substrates. The plasma treatment process does not require the use of solvents, has the advantages of being non-toxic and environmentally friendly, and also avoids the problem of easily damaging the cleaning object in wet cleaning. When the plasma treatment process is used, the entire process flow can be completed within a few minutes, and can be sent to the next process without drying treatment, and can be used for a variety of materials such as high molecular polymers (such as polypropylene, polyvinyl chloride, polytetrafluoroethylene, polyimide, polyester, epoxy resin and other high polymers), metals, semiconductors, oxide surface processing, so in the ABS plastic electroplating process, it can not only be used to remove oil from the surface of the ABS plastic substrate, improve the adhesion between the substrate and the vacuum electroplating coating, but also can be used for post-processing of ABS plastic electroplated parts to improve the silk-screening ability of the metal electroplating layer surface. Therefore, the use of the plasma treatment process can improve the processing efficiency of the entire process line.
[0029] After degreasing the ABS plastic surface, the present invention uses 3-mercaptopropyltrimethoxysilane to modify the ABS plastic substrate. After modification, the surface of the ABS plastic substrate is grafted with mercapto groups, and after ultraviolet irradiation, the mercapto groups can be cross-linked with free radicals in the vacuum electroplating coating component to improve the bonding strength.
[0030] The present invention also provides a vacuum electroplating coating. The present invention uses phosphorus oxychloride, 2-aminobenzothiazole, and acrylamide as raw materials, and reacts in a molar ratio of 1:1:2 to synthesize a flame retardant intermediate, and uses a hydrosilylation reaction to graft 1,1,3,3-tetramethyldisiloxane on two carbon-carbon double bonds of the flame retardant intermediate, and then adds allyl alcohol to block to obtain a dihydroxy silicon-containing flame retardant; then the dihydroxy silicon-containing flame retardant and polyethylene glycol 2000 are mixed and reacted with isophorone diisocyanate to obtain a silicon-containing polyurethane prepolymer, and hydroxyethyl acrylate is added to block to obtain a polyurethane acrylic resin oligomer; the polyurethane acrylic resin oligomer is mixed with other additives to obtain a vacuum electroplating coating. Since the flame retardant is introduced into the vacuum electroplating coating of the present invention, it is not easy to burn, and storage and transportation are safer. The silicone chain segment itself has better flexibility, which can avoid problems such as coating cracking and decreased adhesion due to volume shrinkage and increased stress when the coating is cured; after the coating is cured, the silicone chain segment is more hydrophobic, which improves the water resistance of the coating.
[0031] It should be noted that, when preparing the polyurethane acrylic resin oligomer, the present invention prepares a mixed diol by mixing polyethylene glycol 2000 and a dihydroxy silicon-containing flame retardant in a weight ratio of (3-4):1; then, isophorone diisocyanate is added to the mixed diol in a molar ratio of hydroxyl group to isocyanate group of 1:(1.5-2), and the obtained coating has good flame retardancy and storage stability; if the amount of the mixed diol is increased, the molecular weight of the synthesized polyurethane acrylic resin oligomer will also increase, resulting in poor storage stability of the coating, decreased adhesion to the substrate after curing, and other adverse effects. DETAILED DESCRIPTION
[0032] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making any creative work shall fall within the scope of protection of the present invention.
[0033] Materials used in the present invention and their sources: ABS plastic substrate raw material (article number PA-777B) comes from Taiwan Chi Mei Industrial; photoinitiator 1173 comes from Wuhan Maikairui Chemical Co., Ltd.; defoaming agent (article number DS-210) comes from Foshan Nanhai Datian Chemical Co., Ltd.; leveling agent (article number L-718) comes from Foshan Nuoyu New Material Technology Co., Ltd.
[0034] Embodiment 1: A surface degreasing and electroplating process for ABS plastics, comprising the following steps:
[0035] Step 1:
[0036] Plasma treatment is performed on the surface of the ABS plastic substrate to remove oil stains on the surface of the ABS substrate, thereby obtaining a surface-deoiled ABS plastic substrate; the vacuum degree of the plasma treatment is 100 Pa, the treatment time is 3 min, and the power is 100 W;
[0037] Step 2:
[0038] 5 kg of anhydrous ethanol, 1 kg of deionized water, 60 g of ammonia water, and 50 g of 3-mercaptopropyltrimethoxysilane were mixed, reacted in a water bath at 55° C. for 2 h, and allowed to stand for 5 min after the reaction to obtain a mixed solution; a surface-degreased ABS plastic substrate was placed in the mixed solution, soaked for 1 h, then taken out, rinsed with anhydrous ethanol and deionized water, and dried to obtain a mercapto-grafted ABS plastic substrate;
[0039] Step 3:
[0040] S1: Under nitrogen environment, phosphorus oxychloride was dissolved in tetrahydrofuran, triethylamine was used as an acid binding agent, 2-aminobenzothiazole was added in an ice bath at 0°C for 2h, the temperature was raised to 30°C for 3h, acrylamide was added, the temperature was further raised to 45°C for 10h, and a flame retardant intermediate was obtained; wherein the molar ratio of phosphorus oxychloride, 2-aminobenzothiazole and acrylamide was 1:1:2;
[0041] S2: The flame retardant intermediate and 1,1,3,3-tetramethyldisiloxane are mixed and dispersed in tetrahydrofuran, and an isopropanol solution of chloroplatinic acid is used as a catalyst, and the mixture is reacted at 55° C. in an argon environment for 8 hours, and allyl alcohol is added for end-capping reaction for 6 hours to obtain a dihydroxy silicon-containing flame retardant; wherein the molar ratio of the flame retardant intermediate, 1,1,3,3-tetramethyldisiloxane, and allyl alcohol is 1:2:2;
[0042] S3: Polyethylene glycol 2000 and dihydroxy silicon-containing flame retardant are mixed in a weight ratio of 3:1 to obtain a mixed diol; isophorone diisocyanate is added to the mixed diol in a molar ratio of hydroxyl group to isocyanate group of 1:1.5, dibutyltin dilaurate is used as a catalyst, and the mixture is reacted at 70°C for 2 hours to obtain a silicon-containing polyurethane prepolymer, and the temperature is reduced to 50°C, and hydroxyethyl acrylate is added to the silicon-containing polyurethane prepolymer in a molar ratio of hydroxyl group to isocyanate group of 1:1, and the mixture is reacted for 1 hour to obtain a polyurethane acrylic resin oligomer;
[0043] S4: 56 g of polyurethane acrylic resin oligomer, 5 g of methyl methacrylate, 10 g of 1,6-hexanediol diacrylate, 7 g of trimethylolpropane trimethacrylate, 2 g of photoinitiator, 1 g of defoamer, 0.5 g of leveling agent, 0.5 g of ethylene glycol propyl ether, 12 g of ethyl acetate, 9 g of butyl acetate, 8 g of isobutyl alcohol, and 22 g of deionized water were mixed, and filtered through a 400-mesh gauze to obtain a vacuum electroplating coating;
[0044] Step 4:
[0045] The vacuum plating coating is sprayed on the thiol-grafted ABS plastic substrate at a spraying pressure of 4kg / cm 2 The spraying distance was 10 cm, the spraying thickness was 8 μm, and it was dried naturally for 2 min after spraying, dried in an oven at 50 ° C for 3 min, and then UV cured with an exposure energy of 600 mJ / cm 3 , the processing time is 10s; vacuum electroplating is performed at 50°C to form a metal electroplating layer with a thickness of 30μm, and an ABS plastic electroplated part is obtained;
[0046] Step 5:
[0047] The ABS plastic electroplated parts were treated with plasma. The vacuum degree of the plasma treatment was 158Pa, the treatment time was 3min, and the power was 897W.
[0048] Embodiment 2: A surface degreasing and electroplating process for ABS plastics, comprising the following steps:
[0049] Step 1:
[0050] Plasma treatment is performed on the surface of the ABS plastic substrate to remove oil stains on the surface of the ABS substrate, thereby obtaining an ABS plastic substrate with deoiled surface; the vacuum degree of the plasma treatment is 110 Pa, the treatment time is 4 min, and the power is 105 W;
[0051] Step 2:
[0052] 5 kg of anhydrous ethanol, 1 kg of deionized water, 60 g of ammonia water, and 50 g of 3-mercaptopropyltrimethoxysilane were mixed, reacted in a water bath at 60° C. for 2.5 hours, and allowed to stand for 8 minutes after the reaction to obtain a mixed solution; a surface-degreased ABS plastic substrate was placed in the mixed solution, soaked for 1.5 hours, and then taken out, rinsed with anhydrous ethanol and deionized water, and dried to obtain a mercapto-grafted ABS plastic substrate;
[0053] Step 3:
[0054] S1: Under nitrogen environment, phosphorus oxychloride was dissolved in tetrahydrofuran, triethylamine was used as an acid binding agent, 2-aminobenzothiazole was added in an ice bath at 3°C for reaction for 2.5h, the temperature was raised to 35°C for reaction for 3.5h, acrylamide was added, the temperature was further raised to 50°C for reaction for 11h, and a flame retardant intermediate was obtained; wherein the molar ratio of phosphorus oxychloride, 2-aminobenzothiazole and acrylamide was 1:1:2;
[0055] S2: The flame retardant intermediate and 1,1,3,3-tetramethyldisiloxane are mixed and dispersed in tetrahydrofuran, and an isopropanol solution of chloroplatinic acid is used as a catalyst, and the mixture is reacted at 60° C. in an argon environment for 9 hours, and allyl alcohol is added for end-capping reaction for 8 hours to obtain a dihydroxy silicon-containing flame retardant; wherein the molar ratio of the flame retardant intermediate, 1,1,3,3-tetramethyldisiloxane, and allyl alcohol is 1:2:2;
[0056] S3: Polyethylene glycol 2000 and dihydroxy silicon-containing flame retardant are mixed in a weight ratio of 3:1 to obtain a mixed diol; isophorone diisocyanate is added to the mixed diol in a molar ratio of hydroxyl group to isocyanate group of 1:1.8, dibutyltin dilaurate is used as a catalyst, and the mixture is reacted at 75°C for 2.5 hours to obtain a silicon-containing polyurethane prepolymer; the temperature is lowered to 55°C, and hydroxyethyl acrylate is added to the silicon-containing polyurethane prepolymer in a molar ratio of hydroxyl group to isocyanate group of 1:1, and the mixture is reacted for 1.5 hours to obtain a polyurethane acrylic resin oligomer;
[0057] S4: 56 g of polyurethane acrylic resin oligomer, 5 g of methyl methacrylate, 10 g of 1,6-hexanediol diacrylate, 7 g of trimethylolpropane trimethacrylate, 2 g of photoinitiator, 1 g of defoamer, 0.5 g of leveling agent, 0.5 g of ethylene glycol propyl ether, 12 g of ethyl acetate, 9 g of butyl acetate, 8 g of isobutyl alcohol, and 22 g of deionized water were mixed, and filtered through a 400-mesh gauze to obtain a vacuum electroplating coating;
[0058] Step 4:
[0059] The vacuum plating coating is sprayed on the thiol-grafted ABS plastic substrate at a spraying pressure of 5kg / cm 2 The spraying distance was 13 cm, the spraying thickness was 8 μm, and it was dried naturally for 2.5 min after spraying, dried in an oven at 55 ° C for 4 min, and then UV cured with an exposure energy of 650 mJ / cm 3 , the processing time is 12s; vacuum electroplating is performed at 55°C to form a metal electroplating layer with a thickness of 30μm, and an ABS plastic electroplated part is obtained;
[0060] Step 5:
[0061] The ABS plastic electroplated parts were treated with plasma. The vacuum degree of the plasma treatment was 158Pa, the treatment time was 3min, and the power was 897W.
[0062] Embodiment 3: A surface degreasing and electroplating process for ABS plastics, comprising the following steps:
[0063] Step 1:
[0064] Plasma treatment is performed on the surface of the ABS plastic substrate to remove oil stains on the surface of the ABS substrate, thereby obtaining an ABS plastic substrate with deoiled surface; the vacuum degree of the plasma treatment is 120 Pa, the treatment time is 5 min, and the power is 110 W;
[0065] Step 2:
[0066] 5 kg of anhydrous ethanol, 1 kg of deionized water, 60 g of ammonia water, and 50 g of 3-mercaptopropyltrimethoxysilane were mixed, reacted in a water bath at 65° C. for 3 h, and allowed to stand for 10 min after the reaction to obtain a mixed solution; a surface-degreased ABS plastic substrate was placed in the mixed solution, soaked for 2 h, taken out, rinsed with anhydrous ethanol and deionized water, and dried to obtain a mercapto-grafted ABS plastic substrate;
[0067] Step 3:
[0068] S1: Under nitrogen environment, phosphorus oxychloride was dissolved in tetrahydrofuran, triethylamine was used as an acid binding agent, 2-aminobenzothiazole was added in an ice bath at 5°C for 3 hours, the temperature was raised to 40°C for 4 hours, acrylamide was added, the temperature was further raised to 60°C for 12 hours, and a flame retardant intermediate was obtained; wherein the molar ratio of phosphorus oxychloride, 2-aminobenzothiazole and acrylamide was 1:1:2;
[0069] S2: The flame retardant intermediate and 1,1,3,3-tetramethyldisiloxane are mixed and dispersed in tetrahydrofuran, and an isopropanol solution of chloroplatinic acid is used as a catalyst, and the mixture is reacted at 65° C. in an argon environment for 10 hours, and allyl alcohol is added for end-capping reaction for 10 hours to obtain a dihydroxy silicon-containing flame retardant; wherein the molar ratio of the flame retardant intermediate, 1,1,3,3-tetramethyldisiloxane, and allyl alcohol is 1:2:2;
[0070] S3: Polyethylene glycol 2000 and dihydroxy silicon-containing flame retardant are mixed in a weight ratio of 3:1 to obtain a mixed diol; isophorone diisocyanate is added to the mixed diol in a molar ratio of hydroxyl group to isocyanate group of 1:2, dibutyltin dilaurate is used as a catalyst, and the mixture is reacted at 80°C for 3 hours to obtain a silicon-containing polyurethane prepolymer; the temperature is lowered to 60°C, hydroxyethyl acrylate is added to the silicon-containing polyurethane prepolymer in a molar ratio of hydroxyl group to isocyanate group of 1:1, and the mixture is reacted for 2 hours to obtain a polyurethane acrylic resin oligomer;
[0071] S4: 56 g of polyurethane acrylic resin oligomer, 5 g of methyl methacrylate, 10 g of 1,6-hexanediol diacrylate, 7 g of trimethylolpropane trimethacrylate, 2 g of photoinitiator, 1 g of defoamer, 0.5 g of leveling agent, 0.5 g of ethylene glycol propyl ether, 12 g of ethyl acetate, 9 g of butyl acetate, 8 g of isobutyl alcohol, and 22 g of deionized water were mixed, and filtered through a 400-mesh gauze to obtain a vacuum electroplating coating;
[0072] Step 4:
[0073] The vacuum plating coating is sprayed on the thiol-grafted ABS plastic substrate at a spraying pressure of 6 kg / cm 2 The spraying distance was 15 cm, the spraying thickness was 8 μm, and it was dried naturally for 3 min after spraying, dried in an oven at 60 ° C for 5 min, and then UV cured with an exposure energy of 800 mJ / cm 3 , the processing time is 15s; vacuum electroplating is performed at 60°C to form a metal electroplating layer with a thickness of 30μm, and an ABS plastic electroplated part is obtained;
[0074] Step 5:
[0075] The ABS plastic electroplated parts were treated with plasma. The vacuum degree of the plasma treatment was 158Pa, the treatment time was 3min, and the power was 897W.
[0076] Comparative Example 1: Deionized water cleaning was used to replace the plasma treatment process, and the other parameters were the same as those in Example 1.
[0077] Step 1:
[0078] The ABS plastic substrate was rinsed with deionized water for 10 minutes, and dried to obtain a surface-degreased ABS plastic substrate; 5 kg of anhydrous ethanol, 1 kg of deionized water, 60 g of ammonia water, and 50 g of 3-mercaptopropyltrimethoxysilane were mixed, reacted in a water bath at 55° C. for 2 hours, and allowed to stand for 5 minutes after the reaction to obtain a mixed solution; the surface-degreased ABS plastic substrate was placed in the mixed solution, soaked for 1 hour, and then taken out, rinsed with anhydrous ethanol and deionized water, and dried to obtain a mercapto-grafted ABS plastic substrate;
[0079] Step 2:
[0080] S1: Under nitrogen environment, phosphorus oxychloride was dissolved in tetrahydrofuran, triethylamine was used as an acid binding agent, 2-aminobenzothiazole was added in an ice bath at 0°C for 2h, the temperature was raised to 30°C for 3h, acrylamide was added, the temperature was further raised to 45°C for 10h, and a flame retardant intermediate was obtained; wherein the molar ratio of phosphorus oxychloride, 2-aminobenzothiazole and acrylamide was 1:1:2;
[0081] S2: The flame retardant intermediate and 1,1,3,3-tetramethyldisiloxane are mixed and dispersed in tetrahydrofuran, and an isopropanol solution of chloroplatinic acid is used as a catalyst, and the mixture is reacted at 55° C. in an argon environment for 8 hours, and allyl alcohol is added for end-capping reaction for 6 hours to obtain a dihydroxy silicon-containing flame retardant; wherein the molar ratio of the flame retardant intermediate, 1,1,3,3-tetramethyldisiloxane, and allyl alcohol is 1:2:2;
[0082] S3: Polyethylene glycol 2000 and dihydroxy silicon-containing flame retardant are mixed in a weight ratio of 3:1 to obtain a mixed diol; isophorone diisocyanate is added to the mixed diol in a molar ratio of hydroxyl group to isocyanate group of 1:1.5, dibutyltin dilaurate is used as a catalyst, and the mixture is reacted at 70°C for 2 hours to obtain a silicon-containing polyurethane prepolymer, and the temperature is reduced to 50°C, and hydroxyethyl acrylate is added to the silicon-containing polyurethane prepolymer in a molar ratio of hydroxyl group to isocyanate group of 1:1, and the mixture is reacted for 1 hour to obtain a polyurethane acrylic resin oligomer;
[0083] S4: 56 g of polyurethane acrylic resin oligomer, 5 g of methyl methacrylate, 10 g of 1,6-hexanediol diacrylate, 7 g of trimethylolpropane trimethacrylate, 2 g of photoinitiator, 1 g of defoamer, 0.5 g of leveling agent, 0.5 g of ethylene glycol propyl ether, 12 g of ethyl acetate, 9 g of butyl acetate, 8 g of isobutyl alcohol, and 22 g of deionized water were mixed, and filtered through a 400-mesh gauze to obtain a vacuum electroplating coating;
[0084] Step 3: Spray the vacuum plating paint onto the thiol-grafted ABS plastic substrate at a spray pressure of 4kg / cm 2 The spraying distance was 10 cm, the spraying thickness was 8 μm, and it was dried naturally for 2 min after spraying, dried in an oven at 50 ° C for 3 min, and then UV cured with an exposure energy of 600 mJ / cm 3 , the treatment time is 10s; vacuum electroplating is carried out at 50°C to form a metal electroplating layer with a thickness of 30μm to obtain an ABS plastic electroplated part; the surface of the ABS plastic electroplated part is rinsed with deionized water for 10min and dried.
[0085] Comparative Example 2: No dihydroxy silicon-containing flame retardant was added, and other parameters were the same as those in Example 2.
[0086] Step 1:
[0087] Plasma treatment is performed on the surface of the ABS plastic substrate to remove oil stains on the surface of the ABS substrate, thereby obtaining an ABS plastic substrate with deoiled surface; the vacuum degree of the plasma treatment is 110 Pa, the treatment time is 4 min, and the power is 105 W;
[0088] Step 2:
[0089] 5 kg of anhydrous ethanol, 1 kg of deionized water, 60 g of ammonia water, and 50 g of 3-mercaptopropyltrimethoxysilane were mixed, reacted in a water bath at 60° C. for 2.5 hours, and allowed to stand for 8 minutes after the reaction to obtain a mixed solution; a surface-degreased ABS plastic substrate was placed in the mixed solution, soaked for 1.5 hours, and then taken out, rinsed with anhydrous ethanol and deionized water, and dried to obtain a mercapto-grafted ABS plastic substrate;
[0090] Step 3:
[0091] S1: adding isophorone diisocyanate to polyethylene glycol 2000 at a molar ratio of hydroxyl group to isocyanate group of 1:1.8, using dibutyltin dilaurate as a catalyst, reacting at 75°C for 2.5 hours to obtain a silicon-containing polyurethane prepolymer, cooling to 55°C, adding hydroxyethyl acrylate to the silicon-containing polyurethane prepolymer at a molar ratio of hydroxyl group to isocyanate group of 1:1, and continuing to react for 1.5 hours to obtain a polyurethane acrylic resin oligomer;
[0092] S2: 56 g of polyurethane acrylic resin oligomer, 5 g of methyl methacrylate, 10 g of 1,6-hexanediol diacrylate, 7 g of trimethylolpropane trimethacrylate, 2 g of photoinitiator, 1 g of defoamer, 0.5 g of leveling agent, 0.5 g of ethylene glycol propyl ether, 12 g of ethyl acetate, 9 g of butyl acetate, 8 g of isobutyl alcohol, and 22 g of deionized water were mixed, and filtered through a 400-mesh gauze to obtain a vacuum electroplating coating;
[0093] Step 4: Spray the vacuum plating paint onto the thiol-grafted ABS plastic substrate at a spray pressure of 5kg / cm 2 The spraying distance was 13 cm, the spraying thickness was 8 μm, and it was dried naturally for 2.5 min after spraying, dried in an oven at 55 ° C for 4 min, and then UV cured with an exposure energy of 650 mJ / cm 3 , the processing time is 12s; vacuum electroplating is performed at 55°C to form a metal electroplating layer with a thickness of 30μm, and an ABS plastic electroplated part is obtained;
[0094] Step 5:
[0095] The ABS plastic electroplated parts were treated with plasma. The vacuum degree of the plasma treatment was 158Pa, the treatment time was 3min, and the power was 897W.
[0096] Comparative Example 3: The amount of the mixed diol in S3 was increased, and the other parameters were the same as those in Example 3.
[0097] Step 1:
[0098] Plasma treatment is performed on the surface of the ABS plastic substrate to remove oil stains on the surface of the ABS substrate, thereby obtaining an ABS plastic substrate with deoiled surface; the vacuum degree of the plasma treatment is 120 Pa, the treatment time is 5 min, and the power is 110 W;
[0099] Step 2:
[0100] 5 kg of anhydrous ethanol, 1 kg of deionized water, 60 g of ammonia water, and 50 g of 3-mercaptopropyltrimethoxysilane were mixed, reacted in a water bath at 65° C. for 3 h, and allowed to stand for 10 min after the reaction to obtain a mixed solution; a surface-degreased ABS plastic substrate was placed in the mixed solution, soaked for 2 h, taken out, rinsed with anhydrous ethanol and deionized water, and dried to obtain a mercapto-grafted ABS plastic substrate;
[0101] Step 3:
[0102] S1: Under nitrogen environment, phosphorus oxychloride was dissolved in tetrahydrofuran, triethylamine was used as an acid binding agent, 2-aminobenzothiazole was added in an ice bath at 5°C for 3 hours, the temperature was raised to 40°C for 4 hours, acrylamide was added, the temperature was further raised to 60°C for 12 hours, and a flame retardant intermediate was obtained; wherein the molar ratio of phosphorus oxychloride, 2-aminobenzothiazole and acrylamide was 1:1:2;
[0103] S2: The flame retardant intermediate and 1,1,3,3-tetramethyldisiloxane are mixed and dispersed in tetrahydrofuran, and an isopropanol solution of chloroplatinic acid is used as a catalyst, and the mixture is reacted at 65° C. in an argon environment for 10 hours, and allyl alcohol is added for end-capping reaction for 10 hours to obtain a dihydroxy silicon-containing flame retardant; wherein the molar ratio of the flame retardant intermediate, 1,1,3,3-tetramethyldisiloxane, and allyl alcohol is 1:2:2;
[0104] S3: Polyethylene glycol 2000 and dihydroxy silicon-containing flame retardant are mixed in a weight ratio of 3:1 to obtain a mixed diol; isophorone diisocyanate is added to the mixed diol in a molar ratio of hydroxyl group to isocyanate group of 1:1.2, dibutyltin dilaurate is used as a catalyst, and the mixture is reacted at 80°C for 3 hours to obtain a silicon-containing polyurethane prepolymer, and the temperature is reduced to 60°C, and hydroxyethyl acrylate is added to the silicon-containing polyurethane prepolymer in a molar ratio of hydroxyl group to isocyanate group of 1:1, and the mixture is reacted for 2 hours to obtain a polyurethane acrylic resin oligomer;
[0105] S4: 56 g of polyurethane acrylic resin oligomer, 5 g of methyl methacrylate, 10 g of 1,6-hexanediol diacrylate, 7 g of trimethylolpropane trimethacrylate, 2 g of photoinitiator, 1 g of defoamer, 0.5 g of leveling agent, 0.5 g of ethylene glycol propyl ether, 12 g of ethyl acetate, 9 g of butyl acetate, 8 g of isobutyl alcohol, and 22 g of deionized water were mixed, and filtered through a 400-mesh gauze to obtain a vacuum electroplating coating;
[0106] Step 4: Spray the vacuum plating paint onto the thiol-grafted ABS plastic substrate at a spray pressure of 6 kg / cm 2 The spraying distance was 15 cm, the spraying thickness was 8 μm, and it was dried naturally for 3 min after spraying, dried in an oven at 60 ° C for 5 min, and then UV cured with an exposure energy of 800 mJ / cm 3 , the processing time is 15s; vacuum electroplating is performed at 60°C to form a metal electroplating layer with a thickness of 30μm, and an ABS plastic electroplated part is obtained;
[0107] Step 5:
[0108] The ABS plastic electroplated parts were treated with plasma. The vacuum degree of the plasma treatment was 158Pa, the treatment time was 3min, and the power was 897W.
[0109] Experiment: Take a 10cm×10cm×0.5cm ABS plastic plate and perform degreasing and electroplating processes according to the methods of Examples 1 to 3 and Comparative Examples 1 to 3, wherein:
[0110] The storage stability test method of vacuum electroplating coating is as follows: take 200g of vacuum electroplating coating, seal it in a stainless steel container, place it in a constant temperature blast drying oven at 110±2℃ for 2 hours, and check its sedimentation gel degree. If there is no sedimentation gel, it can be considered that its storage stability period is good.
[0111] The flame retardant performance test method of vacuum electroplating coating is as follows: the vacuum electroplating coating is applied on a glass plate and cured by ultraviolet light to obtain a glass plate with a size of 140mm×10mm×4mm. 3 The film is tested for limiting oxygen index according to ASTM D2863-97.
[0112] The adhesion performance test method of the cured vacuum electroplating coating and the ABS plastic substrate is as follows: after treating the surface of the ABS plastic substrate according to the schemes in Examples 1 to 3 and Comparative Examples 1 to 3, the vacuum electroplating coating is sprayed and cured to form a film, and a cross-cutting test is performed with reference to GB / T9286-1998. A paint film cross-cutting device is used to cut the cured coating to form 100 regular small squares. During the cutting process, it is ensured that the cross-cutting and longitudinal directions are cut through the substrate surface. The debris on the grid is cleaned with a soft brush, and then the tape is adhered. The tape is torn off in one direction. After tearing three times, the adhesion is judged by the remaining proportion of the small squares. The adhesion level is represented by a number, and the smaller the number, the better the adhesion.
[0113] The test method for the water resistance of the coating after the vacuum plating coating is cured is as follows: according to the schemes in Examples 1 to 3 and Comparative Examples 1 to 3, the vacuum plating coating is coated on the surface of the ABS plastic plate and cured to form a film, then immersed in deionized water for 1 hour and taken out, the surface moisture is absorbed with filter paper, and the coating film is observed to see if it is bubbling, wrinkling, or falling off.
[0114] ABS plastic electroplated parts screen printing effect test: spray screen printing ink (brand: Merida, model: UV9000-H) on a random 1cm×1cm area on the surface of the ABS plastic electroplated parts. After curing, use white cotton gauze dipped in 95wt.% alcohol to wipe the printed pattern back and forth 30 times; if the printed pattern is clear and not blurred, the screen printing effect is qualified, otherwise it is unqualified.
[0115] The experimental results are shown in Table 1.
[0116] Table 1. Test results of various properties of vacuum electroplating coatings and ABS plastic electroplated parts
[0117]
[0118] Conclusion: After the ABS plastic is degreased by the plasma treatment process of the present invention in Example 1, the adhesion between the vacuum plating coating and the ABS substrate is improved, while in Comparative Example 1, the plasma treatment process and surface thiol grafting are not performed, the adhesion between the vacuum plating coating and the ABS substrate is small, and the coating falls off from the surface of the substrate after being soaked in water; in addition, after the surface of the ABS plastic electroplated part is cleaned by the plasma treatment process in Example 1, the surface printing performance is better than that of Comparative Example 1 which is not subjected to the plasma treatment process. The data of Example 2 and Comparative Example 2 show that the dihydroxy silicon-containing flame retardant not only improves the flame retardant properties of the coating, but also enhances the water resistance of the coating after curing and the bonding force between the coating and the ABS substrate; the data of Comparative Example 3 show that after increasing the amount of the mixed diol in S3, the storage stability of the vacuum plating coating obtained decreases, and the coating adhesion grade and coating water resistance of the cured coating decrease.
[0119] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A surface degreasing and electroplating process for ABS plastic, characterized in that: The following steps are involved: Step 1: Plasma treatment is performed on the surface of the ABS plastic substrate to remove oil stains on the surface of the ABS substrate, thereby obtaining a surface-deoiled ABS plastic substrate; Step 2: Anhydrous ethanol, deionized water, ammonia water, and 3-mercaptopropyltrimethoxysilane are mixed, reacted in a water bath at 55-65° C. for 2-3 hours, and allowed to stand for 5-10 minutes after the reaction to obtain a mixed solution; an ABS plastic substrate with degreased surface is placed in the mixed solution, soaked for 1-2 hours, taken out, rinsed with anhydrous ethanol and deionized water, and dried to obtain a thiol-grafted ABS plastic substrate; Step 3: spray the vacuum electroplating coating on the mercapto-grafted ABS plastic substrate, dry it naturally for 2 to 3 minutes after spraying, dry it in an oven at 50 to 60° C. for 3 to 5 minutes, and then perform UV curing; vacuum electroplating forms a metal electroplating layer to obtain an ABS plastic electroplated part; Step 4: Post-processing of ABS plastic electroplated parts.
2. The surface degreasing and electroplating process of ABS plastic according to claim 1, characterized in that: In step 1, the vacuum degree of plasma treatment is 100-120 Pa, the treatment time is 3-5 min, and the power is 100-110 W.
3. The surface degreasing and electroplating process of ABS plastic according to claim 1, characterized in that: In step 2, the weight ratio of anhydrous ethanol, deionized water, ammonia water, and 3-mercaptopropyltrimethoxysilane in the mixed solution is (50-60):10:(0.6-0.8):(0.4-0.5).
4. The surface degreasing and electroplating process of ABS plastic according to claim 1, characterized in that: In step 3, the method for preparing the vacuum electroplating coating comprises the following steps: S1: Under nitrogen environment, phosphorus oxychloride was dissolved in tetrahydrofuran, triethylamine was used as an acid binding agent, 2-aminobenzothiazole was added under ice bath condition of 0-5°C for reaction for 2-3h, the temperature was raised to 30-40°C for reaction for 3-4h, acrylamide was added, the temperature was continued to be raised to 45-60°C for reaction for 10-12h, and a flame retardant intermediate was obtained; S2: The flame retardant intermediate and 1,1,3,3-tetramethyldisiloxane are mixed and dispersed in tetrahydrofuran, and an isopropanol solution of chloroplatinic acid is used as a catalyst, and the mixture is reacted at 55-65° C. in an argon environment for 8-10 hours, and allyl alcohol is added for end-capping reaction for 6-10 hours to obtain a dihydroxy silicon-containing flame retardant; S3: polyethylene glycol 2000 and a dihydroxy silicon-containing flame retardant are mixed to obtain a mixed diol; isophorone diisocyanate is added to the mixed diol at a molar ratio of hydroxyl group to isocyanate group of 1:(1.5-2), dibutyltin dilaurate is used as a catalyst, and the mixture is reacted at 70-80° C. for 2-3 hours to obtain a silicon-containing polyurethane prepolymer; the temperature is lowered to 50-60° C., hydroxyethyl acrylate is added to the silicon-containing polyurethane prepolymer at a molar ratio of hydroxyl group to isocyanate group of 1:1, and the mixture is reacted for 1-2 hours to obtain a polyurethane acrylic resin oligomer; S4: Mix polyurethane acrylic resin oligomer, methyl methacrylate, 1,6-hexanediol diacrylate, trimethylolpropane trimethacrylate, photoinitiator, defoamer, leveling agent, ethylene glycol propyl ether, ethyl acetate, butyl acetate, isobutyl alcohol and deionized water, and filter with 300-400 mesh gauze to obtain vacuum electroplating coating.
5. The surface degreasing and electroplating process of ABS plastic according to claim 1, characterized in that: In S1, the molar ratio of phosphorus oxychloride, 2-aminobenzothiazole and acrylamide is 1:1:
2.
6. The surface degreasing and electroplating process of ABS plastic according to claim 1, characterized in that: In S2, the molar ratio of the flame retardant intermediate, 1,1,3,3-tetramethyldisiloxane, and allyl alcohol is 1:2:
2.
7. The surface degreasing and electroplating process of ABS plastic according to claim 1, characterized in that: In S3, polyethylene glycol 2000 and dihydroxy silicon-containing flame retardant are mixed in a weight ratio of (3-4):1 to obtain a mixed diol.
8. The surface degreasing and electroplating process of ABS plastic according to claim 1, characterized in that: In S4, the amount of each component, by weight, is 40 to 60 parts of polyurethane acrylic resin oligomer, 3 to 5 parts of methyl methacrylate, 6 to 12 parts of 1,6-hexanediol diacrylate, 5 to 8 parts of trimethylolpropane trimethacrylate, 2 to 3 parts of photoinitiator, 0.5 to 1 part of defoaming agent, 0.5 to 1 part of leveling agent, 0.5 to 1 part of ethylene glycol propyl ether, 12 to 15 parts of ethyl acetate, 8 to 10 parts of butyl acetate, 7 to 10 parts of isobutyl alcohol, and 20 to 25 parts of deionized water.
9. The surface degreasing and electroplating process of ABS plastic according to claim 1, characterized in that: In step 3, the spraying pressure is 4-6 kg / cm 2 , spraying distance is 10-15cm, spraying thickness is 7-9μm; UV curing exposure energy is 600-800mJ / cm 3 , the processing time is 10 to 15 seconds; the vacuum plating temperature is 50 to 60°C, and the thickness of the metal plating layer is 20 to 50 μm.
10. The surface degreasing and electroplating process of ABS plastic according to claim 1, characterized in that: In step 4, the post-treatment method is to perform plasma treatment on the surface of the ABS plastic electroplated part, the vacuum degree of the plasma treatment is 150-200 Pa, the treatment time is 3-5 minutes, and the power is 800-900W.